Effect of heat treatment on the properties of HA/BG composite films. Issue 6 (15th April 2018) - Wang, D.G.; Ming, X.C.; Zhang, W.L.; Zhang, J.H.; Chen, C.Z.
Abstract: HA/BG composite films were deposited by pulsed laser, and a post heat treatment at 800 °C was followed to improve the properties of the films. The effect of heat treatment on the properties of PLD films was studied by SEM, XRD, FTIR, scratch test and in vivo test. After heat treatment, the surface morphologies of the films changed greatly, the crystallinity and film-to-substrate bonding strength were all increased, and the ostoinduction ability was improved. Heat treatment at 800 °C for 2 h can promote the growth of acicular structure and formation of c-axis oriented HA. After a 3-month embedding period in shin bone of the rabbit, all the specimens were connected well by new bone tissue, however the film treated for 2 h exhibits better ostoinduction ability in the early stage.